2019
DOI: 10.2147/dddt.s203974
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overexpression of SOX9 alleviates the progression of human osteoarthritis in vitro and in vivo</p>

Abstract: Purpose Recent findings have identified that SOX9 served as a key role during the pathogenesis of osteoarthritis (OA). This study aimed to investigate the mechanisms by which SOX9 regulated the formation of OA in vitro and in vivo. Materials and methods The relative expressions of SOX9 in patients with OA and normal fracture of thighbone were analyzed by real-time-PCR. In vitro, IL-1β induced inflammatory response in human chondrocytes was used to evaluate the function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 34 publications
4
53
0
1
Order By: Relevance
“…A 2019 study demonstrated that altered expression of SOX9 and runt-related transcription factor 2 was correlated with chondrocyte health, with SOX9 expression being reduced in OA chondrocytes [32]. Importantly, a contemporary study using IL-1β-induced primary human chondrocytes and an OA mouse model showed that overexpression of SOX9 could ameliorate the pathogenesis of OA both in vitro and in vivo [33]. Here, we investigated the effect of agonism of GPR120 on SOX9 expression in ATDC5 chondrocytes and found that GW9508 and TUG 891 significantly rescued IL-1β-induced reduced expression of SOX9.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 study demonstrated that altered expression of SOX9 and runt-related transcription factor 2 was correlated with chondrocyte health, with SOX9 expression being reduced in OA chondrocytes [32]. Importantly, a contemporary study using IL-1β-induced primary human chondrocytes and an OA mouse model showed that overexpression of SOX9 could ameliorate the pathogenesis of OA both in vitro and in vivo [33]. Here, we investigated the effect of agonism of GPR120 on SOX9 expression in ATDC5 chondrocytes and found that GW9508 and TUG 891 significantly rescued IL-1β-induced reduced expression of SOX9.…”
Section: Discussionmentioning
confidence: 99%
“…SOX9, as the MR of chondrogenesis, is one of the most crucial TFs for keeping cartilage healthy, and loss of SOX9 is involved in upregulated hypertrophic differentiation, cellular senescence, and decreased ECM production. In vitro, overexpression of SOX9 in CHON-001 chondrocytes resulted in the decreased production of the inflammatory marker TNFα and decreased protein degradation of COL2A1 and SMAD3 [191]. In vivo, overexpression of SOX9 in a surgically induced OA mice model resulted in decreased proteoglycan loss and cartilage destruction, indicating that overexpression of SOX9 might protect against OA.…”
Section: Transcription Factors As Therapeutic Targetsmentioning
confidence: 96%
“…However, Chondrocyte death and matrix loss are discovered in the development of OA [22]. Also, decreased expression of collagen II and SOX9 while increased expression of MMP13 in OA was reported [23]. Interestingly, several recent studies showed that herbs such as setin and scutellarin were found to modulate this process.…”
Section: Discussionmentioning
confidence: 99%